Exchange, Property Rights and Transaction Cost: An Institutional Analysis - MORSELLI, Alessandro (Theoretical and Practical Research in Economic Fields, 2025)
The aim of this paper is to try to highlight that no social system is able to function if it is based only on networks of free contracts stipulated between legally equal contractual parties, and in which each party is supposed to be guided exclusively by its own utilitarian ends. In any developed exchange system, non-contractual components are of fundamental importance. A pure exchange system based solely on contractual relations may not work in practice. However, even if there are non-contractual elements in a contract, these elements do not totally govern transactions. In a modern market economy, the rational calculation of profit and loss is the focus of analysis, but it is possible to criticise the claims of neoclassical economists to conceive rationality as unlimited in its scope. Thus, it is argued that in modern society the analysis of exchange should be conducted through the examination of the symbiotic relationship existing between contractual and non-contractual elements.